2013
DOI: 10.1371/journal.pone.0053112
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Peak Selection by a Benjamini-Hochberg-Based Algorithm

Abstract: A common issue in bioinformatics is that computational methods often generate a large number of predictions sorted according to certain confidence scores. A key problem is then determining how many predictions must be selected to include most of the true predictions while maintaining reasonably high precision. In nuclear magnetic resonance (NMR)-based protein structure determination, for instance, computational peak picking methods are becoming more and more common, although expert-knowledge remains the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
(26 reference statements)
0
24
0
Order By: Relevance
“…Only the genes with adjusted p value, namely, false discovery rate (FDR)<0.0005 were screened out, and defined as DEGs. FDR<0.0005 implies that only less than 0.05 % of significant DEGs are false positive [15], indicating that the results of our DEGs screening are reliable.…”
Section: Degs Screeningmentioning
confidence: 87%
See 1 more Smart Citation
“…Only the genes with adjusted p value, namely, false discovery rate (FDR)<0.0005 were screened out, and defined as DEGs. FDR<0.0005 implies that only less than 0.05 % of significant DEGs are false positive [15], indicating that the results of our DEGs screening are reliable.…”
Section: Degs Screeningmentioning
confidence: 87%
“…Then the raw p values of t-test were adjusted by Benjamini-Hochberg algorithm [15]. Only the genes with adjusted p value, namely, false discovery rate (FDR)<0.0005 were screened out, and defined as DEGs.…”
Section: Degs Screeningmentioning
confidence: 99%
“…It was further reported that miR169 is involved in nitrogen-starvation responses in Arabidopsis (Zhao et al, 2011). GmNFYA3 which is a target gene of miR169, has been reported to be a positive regulator of plant tolerance to drought stress (Abbas et al, 2013). MiR156k is responsive to salt and drought in rice and regulates flowering time and shoot development (Kruszka et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…So far, nuclear magnetic resonance (NMR) spectroscopy [2], [3], [4], [5], [6], [7], [8], [9] and X-ray crystallography [10] have been used to determine protein structures. Pintacuda et al employed lanthanide ions for the determination of protein-ligand binding sites [2].…”
Section: Introductionmentioning
confidence: 99%